Facing Challenges of Discrimination Against Local Religious Beliefs in Indonesia - Ilham Dhiya Ul Haq Ramadhan; Asyif Faozi (JURNAL HUKUM SEHASEN, 2023)
Discrimination against local religious followers in Indonesia remains a recurring issue. Local religions are regarded as beliefs and have not yet been legally recognized as religions. However, adherents of local religions should have the same rights as followers of official religions, without any discrimination. This demonstrates that the government has not fully succeeded in safeguarding the rights of local religious followers and providing them with the expected legal protection as stipulated in the legislation. This research aims to analyze various forms of discrimination and protection, referring to both national and international legal frameworks. The qualitative method, specifically literature review, is employed in this study, gathering data from diverse written sources such as laws, Constitutional Court decisions, international conventions, Article 1945 of the Constitution, as well as relevant cases concerning discrimination against local religions. The research analyzes and connects this information to discuss issues related to local religions in Indonesia. Several challenges are encountered, including the implementation of Constitutional Court decisions regarding legal recognition of belief systems, which have not fully met the needs of local religious followers. The religion column in identity cards (KTP) does not appropriately accommodate local religious adherents, as the implementation regulations still differentiate between religion and belief. Furthermore, a specific case in this research pertains to an incident that occurred in 2021, involving three children who are adherents of the Jehovah's Witness faith. This case exemplifies the discrimination faced by Jehovah's Witness followers and represents the challenges of recognizing local religious beliefs in Indonesia. This research suggests the need for encouragement from various sectors, including the government and society, to foster tolerance and acceptance of differences in Indonesia, thereby realizing Article 28E paragraph 2 of the Constitution as a fundamental guarantee of legal protection against discrimination towards minority religious groups.